Industrial law journal. - Industrial Law Society (Oxford : Oxford University Press, 1972)
Industrial Law Journal is established as the leading periodical in its field, providing comment and in-depth analysis on a wide range of topics relating to employment law. It is essential reading for practising lawyers, academics, and lay industrial relations experts to keep abreast of newly enacted legislation and proposals for law reform. In addition Industrial Law Journal carries commentary on relevant government publications and reviews of books relating to labour law.
"Published on behalf of The Industrial Law Society"--Home page.
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: Labor laws and legislation -- Periodicals